Coordinated Implementation of Chikungunya Virus Reverse Transcription–PCR - Marcus Panning; Remi N. Charrel; Oliver D. Mantke; Olfert Landt; Matthias Niedrig; Sung Sup Park (Emerging Infectious Diseases, 2009)
A preformulated chikungunya virus real-time reverse transcription–PCR, quality-confirmed oligonucleotides, and noninfectious virus controls were distributed by the European Network for the Diagnosis of Imported Viral Diseases. An international proficiency study with 31 participants demonstrated that ad hoc implementation of molecular diagnostics was feasible and successful.